Perceived Islamic work ethics and organisational commitment among Muslim engineers in Perak Tengah and Manjung district - Yushak, Mohamed Shamaun; Rajuddin, Adli Rafai Ahmad; Mohamed, Zakiah; Daud, Khairian Mohamad; Bawadi, Norfazilah; Sarif, Suhaimi Mhd (2011)
Many have argued that the productivity and quality of work of Muslim engineers are lower than their non-Muslim counterparts. Islamic Work Ethics is argued as the main barrier for higher productivity. The study aims to obtain the views of Muslim engineers in Perak Tengah and Manjung Districts whether Islamic Work Ethics (IWE) contributes to lower productivity and quality of work by Muslim professionals. The study distributed questionnaires to the 50 Muslim engineers. The preliminary findings show IWE enhances Muslim engineers’ commitment towards their organisations and also work productivity and quality. Thus, the findings rejected the claim that IWE is the barrier for productivity and work quality. Nevertheless, the study found that the “theomorphic potential” of most Muslim engineers in Perak Tengah and Manjung are not fully realized. Such weakness reduces the conscious to be more careful and thoughtful in producing quality work. The study suggests that Muslim engineers should enhance the cognitive (aql’), affective (nafs’) and normative (syariat) aspects of work with Qur’anic-based Islamic values as demonstrated by Prophet Muhammad P.B.U.H. Future studies should cross examine professionals from other sectors with larger sample size.